Development of a high-speed small-angle infrared thermography system in EAST - Chen, G T; Cao, P; Yang, J H; Liang, R R; Li, L; Sun, Y W; Zhong, F C (Review of scientific instruments, 2023)
A high-speed infrared small-angle infrared thermography system (SATS) has been developed and installed on the Experimental Advanced Superconducting Tokamak (EAST) for measuring the surface temperature of the divertor target to calculate the high heat flux induced by Edge Localized Modes (ELMs) and providing observation means for the further physical study of some key parameters, such as power decay length λq and the characteristic time of different types of ELMs. An endoscopic optical system is applied to realize the SATS for clear imaging of the divertor plate area and protection from the harm of impurity deposition and latent tungsten ablation during discharge. The field of view (FOV) of the endoscopic optical system is designed to be 13° in the horizontal direction and 9° in the vertical direction. As a consequence, ∼35° of coverage of the lower-outer divertor and a small part of the lower-inner divertor in toroidal are covered by the FOV with a spatial resolution of around 2 mm/pixel. This paper presents a detailed description of the new SATS and the preliminary experimental diagnostic results. The radial distribution of heat flux induced by an ELM crash was demonstrated.